The Relationship between Auditory Sensory Gating and Cognitive Functions on Auditory and - Panahi, Rasool; Jarollahi, Farnoush; Akbari, Mehdi; Akbarfahimi, Malahat; Haghani, Hamid (Iranian Journal of Child Neurology, 2019)
Objectives Considering the common neurological origins, there is a relationship between the sensory gating and cognitive functions. However, there is no adequate information on this issue. In this study, auditory event-related potentials and the sensory gating performance were assessed in P50, N100 and P200 waves. Besides, their relationship with cognitive performance in auditory and visual modalities was investigated. Materials & Methods Nineteen normal primary school students (14 boys) were tested in Tehran, Iran from 2017 to 2018. In the auditory modality, the Persian version of the non-word repetition test and monaural selective auditory attention test (mSAAT) were used for assessment of the working memory and selective attention, respectively. In order to evaluate the visual working memory and visual selective attention, Rey-Osterrieth complex figure, selective and divided attention test were used, respectively. A 32-channel EEG system was used for electrophysiological assessment. Results The P50 sensory gating was negatively correlated with the visual selective attention (P=0.034, r=-0.49) and N100 sensory gating was negatively correlated with the auditory working memory (P=0.043, r=-0.48) as well as visual selective attention (P=0.039, r=-0.47). For P200, there was a significant negative relationship with auditory selective attention in the right ear (P=0.034, r=-0.49). Conclusion Sensory gating in children is not a modality-specific phenomenon. Sensory gating in a modality could be associated with cognitive functions in other modalities